IMPLIKASI PEMBERIAN JANGKA WAKTU LIMA TAHUN TERHADAP JAMINAN KEPASTIAN HUKUM PEMEGANG HAK ATAS TANAH DI TENGGARONG KUTAI KARTANEGARA - SEPTINA ARMELYA (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The purpose of this research were to know the implication of 5 year’s rule of law legal security of land right in Tenggarong, Kutai Kartanegara and to know the mecanishm of canceling the land right that canceled by the court. The method of this research used normative law reasearch, were to investigate and study the rules of regulation about list of land right. According to analysis result and theory, the researdier found that law security of the owner of land right related to applied rechtsverwerking institute in article 32 clause 2 in goverment regulation no. 24 in 1997’s was not adequate because the periode of 5 years could be refuted and the canceling of land right by the court given technical guidelines to the land officials to cancel it administratively. The goverment were expected to guarantee the law legal of the owner land right that listed on register that coorporated with BPN (National Land Affairs Agency).Keyword : land rights certificate, legal certainty, Goverment Regulation No. 24 in 1997